Why “home garden” projects don’t always work: Insights from Ethiopia - Hirvonen, Kalle; Headey, Derek D. (2020)
In Ethiopia, the average person eats just 42kg of fruit and vegetables per year. This is far below the WHO recommendation of 146kg per year. Fruits and vegetables are excellent sources of vitamins and minerals, vital for our body. Deficiencies can seriously affect our physical health, increasing the risk of diabetes, cardiovascular diseases and certain types of cancers, which in turn increase the risk of premature death. In Ethiopia, poor quality diets are now considered as one of the main underlying causes in the rise of non-communicable diseases in the country. The problem is fruits and vegetables are often too expensive and unaffordable for most. In Ethiopia, the average household would have to spend more than 10% of their income to meet the international recommendation of two servings of fruits and three servings of vegetables per person per day.